Genetics of Gland-in-situ or Hypoplastic Congenital Hypothyroidism in Macedonia - Zdraveska, Nikolina; Kocova, Mirjana; Nicholas, Adeline K.; Anastasovska, Violeta; Schoenmakers, Nadia (Frontiers in Endocrinology, 2020)
Neonatal screening in Macedonia detects congenital hypothyroidism (CH) with an incidence of 1 in 1,585, and more than 50% of cases exhibit a normally located gland-in-situ (GIS). Monogenic mutations causing dyshormonogenesis may underlie GIS CH; additionally, a small proportion of thyroid hypoplasia has a monogenic cause, such as TSHR and PAX8 defects. The genetic architecture of Macedonian CH cases has not previously been studied. We recruited screening-detected, non-syndromic GIS CH or thyroid hypoplasia cases (n = 40) exhibiting a spectrum of biochemical thyroid dysfunction ranging from severe permanent to mild transient CH and including 11 familial cases. Cases were born at term, with birth weight >3,000 g, and thyroid morphologies included goiter (n = 11), thyroid hypoplasia (n = 6), and apparently normal-sized thyroid. A comprehensive, phenotype-driven, Sanger sequencing approach was used to identify genetic mutations underlying CH, by sequentially screening known dyshormonogenesis-associated genes and TSHR in GIS cases and TSHR and PAX8 in cases with thyroid hypoplasia. Potentially pathogenic variants were identified in 14 cases, of which four were definitively causative; we also detected digenic variants in three cases. Seventeen variants (nine novel) were identified in TPO (n = 4), TG (n = 3), TSHR (n = 4), DUOX2 (n = 4), and PAX8 (n = 2). No mutations were detected in DUOXA2, NIS, IYD, and SLC26A7. The relatively low mutation frequency suggests that factors other than recognized monogenic causes (oligogenic variants, environmental factors, or novel genes) may contribute to GIS CH in this region. Future non–hypothesis-driven, next-generation sequencing studies are required to confirm these findings.